PENGARUH FAMILY CONTROL TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN PADA SEKTOR ANEKA INDUSTRI - Santoso, Anita Carolina (Business Accounting Review, 2014)
This study examines the influence of family control, firm size, sales growth, and firm leverage towards profitability and firmsâ value. Samples were taken from 36 wide ranges of industrial sector companies, listed in Indonesia Stock Exchange, conducted for 2010 â 2012 period. The hypotheses tested by using multiple regression analysis by SPSS. In this study, profitability was measured by ROA and firmâs value was measured by Tobinâs q. The result showed family control is negatively associated with profitability and firmâs value. Firm size had positive effect on firmâs value, but had no affect on profitability. Firm Leverage had negative influence toward profitability, while insignificantly affected firmsâ value. Furthermore, sales growth did not prove to be an explanatory variable on both of profitability and firmsâ value